Building climate-resilient food systems in East and Southeast Asia: Vulnerabilities, responses and financing - Zhou, Yunyi; Chen, Ziqi; Chen, Kevin Z. (Higher Education Press, 2023)
Food system resilience to climate change is uniquely imperative for bringing Sustainable Development Goals within reach and leaving no one behind. Food systems in East and Southeast Asia are interacting with planetary boundaries and are adversely affected by extreme weather-related events. A practical question for East and Southeast Asian stakeholders is how to foster climate-resilient food systems in the face of lingering food system vulnerabilities and policy gaps. This paper reviews food system vulnerabilities and policy responses to climate change. In the policy-based review, this paper compares the economy-wide and agriculture-specific targets of low-carbon development across East and Southeast Asia. With China and member states of the Association of Southeast Asia Nations as case studies, multilevel policies in building and financing climate-resilient food systems are further synthesized. The findings confirm significant differences in agriculture-specific emission goals and public financing supports across East and Southeast Asian nations. With an objective to break practical barriers and finance climate-resilient food systems for the future, this paper recommends defining agriculture-specific greenhouse gas emission goals, reorienting the public finance scheme and enhancing mechanisms for the synergy of public and private resources.